The rumor : a novel - Kara, Lesley (New York, NY : Ballantine Books, 2018)
"When a single mother hears a rumor outside her son's school, she never intends to pass it on. But one casual comment leads to another . . . and now there's no going back. Rumor has it that a notorious killer, a woman who has been released from prison years after her brutal crime, is living under a new identity in Joanna's seaside town. So who is the supposedly reformed murderer now living in their neighborhood? Suspicion falls on everyone. As Joanna becomes obsessed with the case, her curiosity will expose her son and his father to a heartless psychopath who has killed--and may kill again. And she will learn how dangerous one rumor can become . . . and just how far she must go to protect those she loves from harm. She is going to regret the day she ever said a word . . . "--Provided by publisher.
Keywords: Suspense -- Fiction; Contemporary Women -- Fiction